2016
DOI: 10.1111/dote.12489
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs as novel potential biomarkers for esophageal squamous cell carcinoma diagnosis: a meta-analysis update

Abstract: Early detection of esophageal squamous cell carcinoma (ESCC) is urgently needed to reduce the high morbidity and mortality of disease. Circulating microRNAs (miRNAs) are promising molecular biomarkers for ESCC prediction. We performed a comprehensive meta-analysis to systematically evaluate the diagnostic accuracy of circulating miRNAs in diagnosis of ESCC patients. Eligible studies were identified and assessed for quality employing multiple search strategies. Summary estimates for sensitivity, specificity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 49 publications
2
21
1
Order By: Relevance
“…Among them, miR-223 was the most significantly upregulated (fold change, 3.88) and miR-21 had the highest diagnostic value (AUC, 0.80). None of the miRNAs were associated with sex or age, which was in accordance with previous reports (21,58,59). All 5 miRNAs were associated with the T and N TNM stages, with the exception of miR-21, which was associated only with T stage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Among them, miR-223 was the most significantly upregulated (fold change, 3.88) and miR-21 had the highest diagnostic value (AUC, 0.80). None of the miRNAs were associated with sex or age, which was in accordance with previous reports (21,58,59). All 5 miRNAs were associated with the T and N TNM stages, with the exception of miR-21, which was associated only with T stage.…”
Section: Discussionsupporting
confidence: 92%
“…MiRNAs continue to attract research attention for this purpose, and promising diagnostic markers have been identified for breast cancer (13), liver cancer (14), lung cancer (15), colorectal cancer (16), uterine cancer (17), glioma (18) and gastroesophageal cancer (19); a number of such biomarkers function as oncogenes or tumor-suppressor genes (20). Numerous studies have associated various circulating miRNAs with EC (21). However, different research groups have drawn contrasting conclusions regarding the same plasma miRNAs in EC.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that these microRNAs can be used as biomarkers for cancers. Thousands of microRNAs have been discovered, some of which have significant diagnostic and prognostic value in ESCC 16 . To comprehensively analyze the value of microRNAs as biomarkers, we performed a meta-analysis of each microRNA, while more literatures than previous meta-analyses were included.…”
Section: Discussionmentioning
confidence: 99%
“…However, one of the meta-analyses investigated the value of diagnosis and prognosis of single microRNA 12 . Moreover, several researchers combined various microRNAs to get conclusions about the value of all microRNAs in ESCC, but overlooked the heterogeneity in diverse microRNAs from inconsistent sample sources 13 - 16 . Taking into consideration the drawbacks of previous publications, a more integrative meta-analysis of microRNA for ESCC, on the basis of all relevant prior studies, was conducted to acquire a better understanding of the diagnostic and prognostic efficiency of microRNA in ESCC.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, because of their high stability in circulation, blood miRNAs are ideal candidates as biomarkers for noninvasive diagnostic screening and for monitoring of cancer development (14). Although still an emerging area of research, our recent meta-analysis has highlighted the potential use of specific plasma/serum miRNAs in the detection of ESCC (15). However, most of these miRNAs were not further validated in independent case-control studies, and most studies only focused on a single miRNA rather than their combination.…”
Section: Introductionmentioning
confidence: 99%